PENGGUNAAN MEDIA GAMBAR MELALUI MULTIMEDIA SPECTRA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PELAJARAN IPS DI SMK NEGERI 3 TANAH PUTIH TAHUN PELAJARAN 2015/2016 - Hatari, Indra; Haryana, Gani; ', Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to increase the motivation to learn socil subject with the use of media images through multimedia Spectra in class X SMK Tanah Putih 3 with totaling 20 people students. The research was conducted in two cycles in which the data were collected through observation of teacher activity, student activity observation and student motivation during the learning process. The results showed that the use of media images through multimedia spectra can increase learning motivation IPS. It proved the observation of each cycle has increased. The results obtained for the first cycle of teacher activity with a percentage of 65% increase in the second cycle to 85%. Along with the increased activity of teachers in the second cycle, the student activity also increased, in the first cycle of activity students gain a percentage of 56.00% and increased to 85.00%. Students' motivation has also seen rising. This is evident from the percentage of student motivation in the first cycle with the percentage of 50.63%, the percentage increased to 78.13%. Based on these results indicate that by using media images through multimedia spectra increase students' motivation in social studies.Keywords: Media images, Spectra Multimedia and Motivation